The Impact of Gender on Anthropometric Measures of Twins. (21st July 2016) - Jahanfar, Shayesteh; Lim, Kenneth
Abstract : Introduction: Literature suggests that male hormones influence fetal growth in singleton pregnancies. We hypothesized that the same phenomenon is seen in twin gestations. Objectives: (1) to identify the impact of gender associated with fetal birth weight, head circumference, and birth length for twins; (2) to examine the effect of gender on standardized fetal growth at birth, according to gestational age and birth order; (3) to examine the effect of gender on placenta weight and dimensions. Methodology: This was a population-based retrospective cohort study of twins (4, 368 twins, 2, 184 pairs) born in British Columbia, Canada from 2000–2010. We excluded twins with stillbirth, congenital anomalies, and those delivered with cesarean section. We also controlled for confounding factors, including birth order, gestational age, maternal anthropometric measures, maternal smoking habits, and obstetric history. A subsample of this population was analyzed from Children and Women Hospital to obtain chorionicity information. Results: Male–male twins were heavier than male–females and female–female twin pairs ( p =.01). Within sex-discordant twin pairs, males were also heavier than females ( p =.01). Regression analysis suggested that gender affects birth weight independent of birth order and gestational age. Other newborn anthropometric measures were not found to be dependent on gender. In analyzing a subsample with chorionicity data, birth weight was the only anthropometric measure that was both statistically and clinically affected by sex, even after adjustment for gestational age, chorionicity, birth order, and maternal age. Conclusion: Birth weight was affected by gender while head circumference and birth length were not.